IMPROVING VISUAL-SPATIAL ABILITY IN MATHEMATICS THROUGH MATCHING SHAPES - Aprian Subhananto (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to detect Matching Shape that can improve visual spatial math skills in Natural Academy early childhood. This type of research is classroom action research. This research was carried out with a cycle model. The subject of this research is early childhood at Natural Academy. The data collection techniques used in this research are picture matching tests, and observation of teacher and student activities to analyze the quality of the application of learning with matching shapes. The data in this study were analyzed by descriptive analysis. The results of this study showed an increase in visual spatial ability through matching shapes. This is evidenced by the initial ability reaching an average value of 55.5, in cycle I reaching an average value of 70 and cycle II reaching an average value of 89.1. Meanwhile, the initial observation of the quality of teacher activities was 39.6% and students were 20%, cycle I reached 59% of teacher activities while students were 56%. Then in cycle II it reached 89% of teacher activities and 90% of student activities.